MODEL PENGEMBANGAN KEPRIBADIAN GURU BERBASIS ETIKA PROFETIK SEBAGAI FONDASI PENDIDIKAN HUMANISTIK ISLAM - Amelia cahyaeti; Ghinan Muhammad Zainie; Harina Novira Fitriani; Putri Awaliah Nursakinah; Mursidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is grounded in the concern over the declining moral and spiritual quality of teachers, which weakens the humanistic orientation of Islamic education. It aims to explore how a prophetic ethics based model can develop teacher personality and how it integrates with Islamic humanistic education. The research uses a qualitative approach with a library research design, relying on primary sources such as the Qur’an and Hadith, and supported by relevant academic literature. Data were collected through documentation and analyzed using content analysis combined with an interpretative-conceptual approach. The findings show that the development of teacher personality based on prophetic ethics is built on key values, namely shiddiq, amanah, tabligh, and fathanah, as well as the pillars of humanization, liberation, and transcendence. This model emphasizes internalization of values, holistic development, and exemplary behavior in teaching practice. The study concludes that integrating prophetic ethics with Islamic humanistic education produces teachers who are morally grounded, spiritually aware, and professionally competent. The impact of this model is the creation of a more humanistic, value-oriented learning environment and the strengthening of students’ character, particularly in terms of honesty, responsibility, and social awareness